Movement and consumptive demand of the introduced flathead catfish Pylodictis olivaris in the upper Gila River basin, New Mexcio, and potential impacts on native fishes - Hedden, Skyler C. (Kansas State University, 2015)
Negative interactions with nonnative fish are often cited as a leading cause of declining native fish populations, but quantifying these interactions is difficult. Movement ecology and consumptive demand estimates of nonnative fish predators is needed to better understand potential impacts these organisms are having on native species. The objective of this thesis were to estimate the consumptive demand of Flathead Catfish Pylodictis olivaris on native fishes across an elevational gradient, and characterize the movement at hourly, daily, and seasonal scales of this introduced predator. This research was conducted in the upper Gila River basin of southwestern New Mexico. Bioenergetics modeling was used to estimate consumptive demand; model results were coupled with measured densities and size structure of Flathead Catfish populations, and water temperatures, to predict its predatory threat. Potential consumption was highest at lower elevation sites because of higher water temperatures, but actual consumption was highest at mid-elevation sites because of the prevalence of large-bodied individuals. Potential annual consumptive demand of Flathead Catfish on native fish across our nine sampling sites ranged from 0.0 to 3.1 g/m²/yr, which exceeded native fish productivity at one site. To characterize the movement of Flathead Catfish, we used radio telemetry and tracked individuals from May 2014 to June 2015. Movement behaviors varied among individuals with a majority moving <150 m from capture location and some more mobile, moving substantial distances (692-42,840 m). During the course of the study, activity was greatest in summer and fall, and individuals moving substantial distances moved downstream to warmer river reaches before the winter. Nightly movements only involved short distances (5 m) and no fish exceeded a single movement >80 m. Daily activity was greatest during evening but late afternoon activity was observed in summer and fall. Results from this study identify areas within the upper Gila River where introduced Flathead Catfish consumption is likely to negatively impact native fish populations and managers can use this information to understand potential overlap with native species, target future removal efforts in areas where these fish are concentrated, and avoid stocking native fishes in reaches where Flathead Catfish tend to aggregate.
Keywords: Bioenergetics; Fish movement; Native fish conservation; Biology (0306)